Perception of The Elderly In Traveling In The Digital Age - Wakarmamu, Thobby; Haryanti, Nik (International Journal of Educational Research & Social Sciences, 2022)
Digitization of tourism is considered very crucial if a country wants to capture the growth opportunities of the tourism sector. Tourist destinations can be searched online, offering convenience for the public, especially elderly tourists who want a comfortable and pleasant tourist spot in their spare time or on vacation. For elderly foreign tourists will choose to do outdoor activities if the temperature has started to warm. Tourist attractions with beaches that have warm temperatures are certainly suitable for the atmosphere of elderly tourists to spend their leisure time. The purpose of this research is to find out the perception of the elderly in traveling in the digital era. The research method is descriptive research is not intended to test certain hypotheses, but only describes what it is about a variable, symptom or condition. The data collection technique is using a questionnaire. The results of the research show that the perception of the elderly in traveling in the digital era can be seen from the results: 1) The assessor factor is in the High category, 2) Viewed from the situational factor in the Very High category and seen from the target factor in the Very High category. Thus tourist attractions that are traced through social media or the internet by elderly tourists use the latest technology in seeing the development of tourist attractions, seeing the uniqueness, comfort level, security in accordance with reality so that they can find information on tourist attractions, state of facilities, so look for tourist attractions that can be visited. provide complete facilities and attractive conditions. The results of the research show that the perception of the elderly in traveling in the digital era can be seen from the results: 1) The assessor factor is in the High category, 2) Viewed from the situational factor in the Very High category and seen from the target factor in the Very High category. Thus tourist attractions that are traced through social media or the internet by elderly tourists use the latest technology in seeing the development of tourist attractions, seeing the uniqueness, comfort level, security in accordance with reality so that they can find information on tourist attractions, state of facilities, so look for tourist attractions that can be visited. provide complete facilities and attractive conditions. The results of the research show that the perception of the elderly in traveling in the digital era can be seen from the results: 1) The assessor factor is in the High category, 2) Viewed from the situational factor in the Very High category and seen from the target factor in the Very High category. Thus tourist attractions that are traced through social media or the internet by elderly tourists use the latest technology in seeing the development of tourist attractions, seeing the uniqueness, comfort level, security in accordance with reality so that they can find information on tourist attractions, state of facilities, so look for tourist attractions that can be visited. provide complete facilities and attractive conditions. 2) Judging from the situational factors in the Very High category and judging from the target factors in the Very High category. Thus tourist attractions that are traced through social media or the internet by elderly tourists use the latest technology in seeing the development of tourist attractions, seeing the uniqueness, comfort level, security in accordance with reality so that they can find information on tourist attractions, state of facilities, so look for tourist attractions that can be visited. provide complete facilities and attractive conditions. 2) Judging from the situational factors in the Very High category and judging from the target factors in the Very High category. Thus tourist attractions that are traced through social media or the internet by elderly tourists use the latest technology in seeing the development of tourist attractions, seeing the uniqueness, comfort level, security in accordance with reality so that they can find information on tourist attractions, state of facilities, so look for tourist attractions that can be visited. provide complete facilities and attractive conditions.